Acidic soil amelioration strategies for improving soil fertility: a systematic literature review of techniques, materials, and mechanisms - Ezra Delfianza; Fitri Khoerunnisa (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2026)
Declining agricultural productivity in tropical and subtropical regions is largely due to high soil acidity, which inhibits nutrient availability and increases the solubility of toxic elements such as aluminum and iron. Acidic soil is one of the main constraints in agricultural systems, characterized by low soil pH and an imbalance of essential nutrients for plants. This study aimed to systematically review various approaches to acid soil amelioration, focusing on the mechanisms and materials used. The method used in this study was a Systematic Literature Review (SLR), through an analysis of 38 reputable scientific articles published between 2021 until 2025 and indexed in the Scopus database. The article selection process was based on inclusion criteria specifically related to the results of acidic soil amelioration research. The synthesis results show that acidic soil amelioration approaches could be grouped into several main categories, namely liming-based, biochar-based, biochar and organic-based, organic (non-biochar)-based, organomineral-based, and industrial waste-based. Although research on acid soil amelioration has developed rapidly, there was still considerable variation in the selection of materials, composition, and application methods used. Overall, this systematic literature review provides a structured overview of the mechanisms and materials used in acid soil amelioration.